Rancang Bangun Mesin Pengupas Kulit Lada Menggunakan Cutter Rubber Pad - Susilawati Susilawati; Rivandra Rezani; Imam Mutaqim; Suparman Sutaryat (Department of Mechanical Engineering Education, 2020)
Surian Subdistrict, especially in Mekarsari village, has the largest potential of pepper production in Sumedang Regency. The full potential has not been achieved due to lack of mechanization in the pepper production. Currently, the peeling process of peppercorns uses manual hand rubbing, which is inefficient and causing tiredness and skin irritation. The purpose of this research is to design and build a peppercorn peeling machine to increase productivity. The design process used Autodesk Inventor 2015 CAD software. The machine-building process comprised of design actualization, Work Preparation planning, tools and materials preparation, machining and fabrication process and test run. The result of the design is a peeling machine having dimensions (l x w x h) of 993 x 590 x 670 mm. The machine is equipped with a 5.5 HP and 3600 rpm motor drive which yields in 28 kg/hour pepper production capacity. The working principle of this machine is to grind the peppercorns in the filter and then the cutter cuts and separates the pepper seeds from its shell.Kecamatan Surian memiliki potensi penghasil lada terbesar di Kabupaten Sumedang, khususnya di Desa Mekarsari (Yosini, 2018: 105-115). Permasalahan petani lada adalah masih secara manual dalam pengupasan kulit lada. Proses yang dilakukan hanya menggunakan kedua telapak tangan dalam menggosok buah lada sehingga memerlukan waktu yang lama dan menyebabkan kelelahan dan iritasi pada kulit telapak tangan. Tujuan penelitian ini adalah merancang dan membuat mesin pengupas kulit lada agar dapat membantu petani lada dalam meningkatkan produktivitasnya. Teknik perancangan menggunakan software Autodesk Inventor 2015. Proses manufaktur dilakukan melalui tahapan pembacaan desain, pembuatan work preparation, persiapan alat dan bahan, proses manufaktur hingga uji kinerja. Hasil penelitian yaitu dihasilkan mesin pengupas kulit lada dengan dimensi panjang 993 mm, lebar 590 mm dan tinggi 670 mm dengan motor 5,5 HP dan putaran 3.600 rpm dan kapasitas 28 kg/jam. Prinsip kerja mesin ini yaitu menggiling lada yang terdapat pada filter kemudian cutter bertabrakan dengan lada sampai terpisah dengan kulitnya.